(untitled) (KYAMC Journal, 2025)
Background: Studying the prevalence of vitamin D deficiency in pregnant women and its relationships to parity, BMI, and employment status was the study’s goal. Materials and Methods: An observational study was carried out in the Department of Gynecology and Obstetrics at Khwaja Yunus Ali Medical College Hospital (KYAMCH), Enayetpur, Sirajganj, Bangladesh, between December 2023 and July 2024. The study involved 188 pregnant women who gave informed consent. On their initial visit, blood was drawn, and in the hospital lab, an automated immunoassay analyzer was used to measure the patient’s 25 (OH) D3 level. Results were then tabulated and analyzed. Results: Of the 188 pregnant women, only 14 (or 7.50%) had levels of vitamin D between 30 and 100 ng/ml, that is a sufficient level of vitamin D3. Within this group, the mean (SD) level of vitamin D was 41.1±10.8. Of the study individuals, 48 (25.6%) had vitamin D insufficiency (20-29 ng/ml) with a mean (SD) value of 22.6±2.3, and 126 (68.87%) had vitamin D deficiency with serum level <20 ng/ml and a mean (SD) value of 13.8±3.9. The combined amount of vitamin D insufficiency (less than 30 ng/ml) and deficiency made up 92.50%, with a mean (SD) of 16.2±5.6. Out of the group of people lacking in vitamin D, 26 (16.25%) had a mean of 8.1±1.3 and a vitamin D level less than 10 ng/ml. Conclusion: Vitamin D inadequacy and insufficiency are highly prevalent among pregnant women attending OPD at KYAMCH, a tertiary care hospital in Northern region of Bangladesh. Correcting vitamin D insufficiency during pregnancy is important because it plays a critical role in the health outcomes for both the mother and the fetus. KYAMC Journal Vol. 15, No. 04, January 2025: 169-172